2015
DOI: 10.1007/s12126-015-9224-4
|View full text |Cite
|
Sign up to set email alerts
|

Silver Surfers Search for Gold: a Study Into the Online Information-Seeking Skills of Those Over Fifty

Abstract: Older adults are now the fastest growing population of online users the world over (Olson et al. Ageing International, 36(1), 123-145, 2011). Encouraging data continues to emerge regarding the rate of Internet adoption among those over fifty in particular (Hernandez-Encuentra et al. Educational Gerontology, 35 (3), [226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245] 2009). Yet questions as to the effectiveness of such use and of training designed to advance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…OHI can be incomplete, inaccurate, outdated, and even plain wrong and misleading (Haluza et al, 2017). Furthermore, Internet users are largely left to themselves to interpret OHI and determine its reliability and relevance (Morrison, 2015). People who lack the necessary skills and media, Internet, and (e-)health literacy to access, understand, and appraise OHI might misinterpret or misuse it (Chung, 2013;Gualtieri, 2009;Iverson et al, 2007;Lee et al, 2014;Silver, 2015).…”
Section: Ohimentioning
confidence: 99%
See 2 more Smart Citations
“…OHI can be incomplete, inaccurate, outdated, and even plain wrong and misleading (Haluza et al, 2017). Furthermore, Internet users are largely left to themselves to interpret OHI and determine its reliability and relevance (Morrison, 2015). People who lack the necessary skills and media, Internet, and (e-)health literacy to access, understand, and appraise OHI might misinterpret or misuse it (Chung, 2013;Gualtieri, 2009;Iverson et al, 2007;Lee et al, 2014;Silver, 2015).…”
Section: Ohimentioning
confidence: 99%
“…Concurrently, using the Internet for health (information) purposes has been negatively associated with older age (Galarce et al, 2011;Hunsaker & Hargittai, 2018;Miller & Bell, 2012;Thompson et al, 2004;Xie, 2009). Individual age-related factors such as impaired vision and declining cognitive abilities (Czaja et al, 2010;Morrison, 2015;Xie, 2009) as well as functional literacy decline have been linked to difficulties using the Internet and finding and understanding OHI (Friemel, 2016;Huang et al, 2012;Hunsaker & Hargittai, 2018;Lee, Hoti, Hughes, & Emmerton, 2015;Scott et al, 2017). Importantly, Silver (2015) found that adults over 50 years of age have various concerns with using the Internet in relation to health issues.…”
Section: Age and Internet Usementioning
confidence: 99%
See 1 more Smart Citation
“…Medical advice offered by for-profit companies and celebrities may not be scientifically sound and could be harmful [ 16 - 19 ]. Also, health information websites may not be senior friendly [ 20 , 21 ]. Lastly, most health websites focus on specific diseases or health conditions without providing a broader view of aging by including content on disease prevention or health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of various search engines reveal that people of all ages have difficulties using them. For example, seniors seem to have difficulty in finding the information they want about search engines (Morrison, 2015). Aula, Khan, and Guan (2010) found that as task difficulty increases, users issue more queries and are more likely to visit more Web pages and spend more time on search engine result pages.…”
Section: Teaching Interventionmentioning
confidence: 99%